Flames of transformation: Igniting better mental and physical health for racialized and gendered North Americans - Farah Mahrukh Coomi Shroff; Farah Mahrukh Coomi Shroff (Frontiers Media S.A., 2023)
COVID-19 is catalyzing both crises and opportunities for communities of color.1 The crisis of high mental and physical morbidities and mortalities exposes persistent inequities while providing opportunities to celebrate the power of rejuvenated anti-racism movements, fueled partly in response to the extremism of ultra-conservative governments, the circumstances to reflect deeply on racism because of forced stay-at-home-orders, and digital technologies primarily driven by youth. In marking this historical moment of longstanding anti-racism and decolonial struggles, I assert the importance of foregrounding women's needs. In analyzing racism, rooted in colonialism and white supremacy, and its impacts on mental and physical health status, I focus on improving racialized women's lives within the larger context, concentrating on the determinants of health. I contend that fanning the flames to scathe the racist and sexist foundations of North American society will break new ground for sharing wealth, bolstering solidarity and sisterhood, and ultimately improving Black, Indigenous, and Women of Color (BIWOC) health. Canadian BIWOC earn approximately 59 cents to the dollar earned by non-racialized men, creating vulnerabilities to economic downturns, such as the one Canada is currently in. BIWOC care aides, at the bottom of the healthcare hierarchy, are emblematic of other Black, Indigenous, and People of Color (BIPOC), who face risks of frontline work, low wages, poor job security, unpaid sick days and so forth. To that end, policy recommendations include employment equity initiatives that hire groups of racialized women who consciously express solidarity with each other. Cultural shifts within institutions will be key to providing safe environments. Improving food security, internet access and BIWOC-related data collection linked to community-based programming while prioritizing research on BIWOC will go a long way toward improving BIWOC health. Addressing racism and sexism within the healthcare system, aiming for equitable diagnostic and treatment foci, will require transformative efforts including determined leadership and buy-in from all levels of staff, long-term training and evaluation programs, audited by BIPOC communities.